0.5(х-3)=0.6(4+х)-2.6
0.5х-1.5=2.4+0.6х-2.6 0.5х-0.6х=2.4-2.6+1.5
-0.1х=1.3 х=-13
0.5(х-3)=0.6(4+х)-2.60.5х-1.5=2.4+0.6х-2.60.5х-0.6х=2.4-2.6+1.5-0.1х=1.3х=-13Ответ: х=-13

Ответы и объяснения

Лучший Ответ!
2013-08-12T12:12:33+04:00
0.5(x-3)=0.6(4+x)-2.6
0,5x-1,5=2,4+0,6x-2,6
0,5x-0,6x=1,5+2,4-2,6
-0,1x=1,3
x=-13





ну так ты всё это распиши
ту все і так ясно шо ше розписати!!!!!!!!!!!!!!
невідомі в ліву частину відомі в праву
ладно спасибо
ты украинец?
2013-08-12T12:17:11+04:00
0,5х-1,5=2,4+0,6х-2,6
0,5х-1,5-0,6х-0,2=0
-0,1х=1,7
х=-17